Interactivist Refutation of Radical Epistemic Skepticism Characteristic of Postmodern Literary Studies and Fiction (ENTHYMEMA, 2023)
Postmodern fiction and literary theory have endorsed radical skepticism about knowledge, which was partly conditioned by philosophers’ inability to provide a viable epistemology that would resolve the radical skeptical problems. Most recent developments in both fiction and theory have largely ignored the apparently still unresolved issue and have instead embraced the position of active commitment that presupposes that knowledge is in fact possible. In this text, we address this apparent oversight and present an interactivist ontology of the mind and culture that explains how we can acquire knowledge about the world, and why the postmodern radical skepticism is ungrounded. We argue that once the interactivist theory of cognition as well as ontology of the mind and culture are assumed, the skeptical problems that troubled postmodern thought become non-problems and further pursuit of epistemically evaluable theory of culture (fiction included) gains solid theoretical grounds.
Keywords: Postmodern skepticism; Interactivism; Cognition; Truth